2014
DOI: 10.1063/1.4890010
|View full text |Cite
|
Sign up to set email alerts
|

Direct tunneling through high-κ amorphous HfO2: Effects of chemical modification

Abstract: We report first principles modeling of quantum tunneling through amorphous HfO2 dielectric layer of metaloxide-semiconductor (MOS) nanostructures in the form of n-Si/HfO2/Al. In particular we predict that chemically modifying the amorphous HfO2 barrier by doping N and Al atoms in the middle region -far from the two interfaces of the MOS structure, can reduce the gate-to-channel tunnel leakage by more than one order of magnitude. Several other types of modification are found to enhance tunneling or induce subst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Figure 5 intuitively show the band alignment of ZnO/Zn 0.85 M 0.15 O (M = Mg, Cd) by plotting the local projected DOS4243 along the heterojunction direction. It can be clearly observed that the pure ZnO crystal formed type-I band alignment heterojunction with its Mg and Cd doped ternary alloys, and the band gap of pure ZnO is smaller than that of ZnMgO but larger than that of ZnCdO.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5 intuitively show the band alignment of ZnO/Zn 0.85 M 0.15 O (M = Mg, Cd) by plotting the local projected DOS4243 along the heterojunction direction. It can be clearly observed that the pure ZnO crystal formed type-I band alignment heterojunction with its Mg and Cd doped ternary alloys, and the band gap of pure ZnO is smaller than that of ZnMgO but larger than that of ZnCdO.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the limitation of structure size in the first principles calculation, we performed an empirical WKB fitting with parameters obtained from the DFT calculations to predict the pressure-dependent conductance of pure BP devices at larger scales. Using the WKB method, the conductance G WKB can be estimated empirically by [4650]…”
Section: Resultsmentioning
confidence: 99%
“…Besides using the above calculation method to accurately determine the band offset values, a more intuitive way to obtain the band alignment is to calculate the local projected density of states (LPDOS) of the heterojunction [56][57][58], through which we can obtain the band alignment of the heterojunction directly, and an intrinsic staggered band offset (type II band alignment) can be observed as shown in Figure 4. Clearly, the LPDOS indicated band offsets qualitatively agree well with our accurately determined band offset values.…”
Section: Resultsmentioning
confidence: 99%